2016
DOI: 10.2105/ajph.2016.303089
|View full text |Cite
|
Sign up to set email alerts
|

Disability-Free Life Expectancy Over 30 Years: A Growing Female Disadvantage in the US Population

Abstract: Objectives To examine changes in active life expectancy in the United States over 30 years for older men and women (aged ≥ 65 years). Methods We used the 1982 and 2004 National Long Term Care Survey and the 2011 National Health and Aging Trends Study to estimate age-specific mortality and disability rates, the overall chances of survival and of surviving without disability, and years of active life for men and women. Results For older men, longevity has increased, disability has been postponed to older age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 38 publications
7
73
1
5
Order By: Relevance
“…Largely due to data constraints, prior studies have focused on shorter (generally 10- or 20-year) time periods and have not emphasized race. On balance our findings are consistent with prior studies, which have found compression of disability at age 65 during the 1980s and 1990s [22]. By focusing on racial differences, however, we find that the compression – defined as an increase in the percentage of remaining life to be lived without disability – has been experienced by whites but not blacks at older ages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Largely due to data constraints, prior studies have focused on shorter (generally 10- or 20-year) time periods and have not emphasized race. On balance our findings are consistent with prior studies, which have found compression of disability at age 65 during the 1980s and 1990s [22]. By focusing on racial differences, however, we find that the compression – defined as an increase in the percentage of remaining life to be lived without disability – has been experienced by whites but not blacks at older ages.…”
Section: Discussionsupporting
confidence: 91%
“…Such measures convey whether survival changes are accompanied by a compression or expansion in the period spent without activity limitations (or “disability-free”). Indeed, several studies have pointed to a pattern consistent with an overall compression of morbidity through the 1980s and 1990s, particularly for those with higher educational attainment [21,22]. However, studies focused on trends in active life expectancy by race are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent work has been able to address this question by asking whether modern advances in medicine have been more successful in extending disability-free life (healthspan) or activity-limited life (gerospan). There is evidence that, especially for females, medical advances have prolonged longevity primarily by expanding the late-life period of morbidity, without much effect on the span of disability-free life (Freedman et al, 2016). Fundamentally, however, whether it is worthwhile to extend lifespan in this fashion is a value judgment that may vary between individuals, and is thus more in the realm of clinical decision analysis (Kassirer, 1976; Weinstein and Stason, 1977; Lee et al, 2009) than experimental biology.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, mulheres idosas apresentam uma maior tendência a apresentarem deficiências na vida tardia. Nos Estados Unidos da América, porém, com o passar das décadas, foi observada uma diminuição das diferenças na expectativa de vida entre os gêneros (29).…”
Section: Continuação Da Tabelaunclassified